Pendayagunaan Dana Zakat, Infak dan Sedekah dalam Program Kotim Sejahtera pada Baznas Kabupaten Kotawaringin Timur - Hafiz, Ahmad; Nurani, Muhammad Fahmi (Sharia Journal and Education Center Publishing, 2024)
Abstract This research is motivated by the problem of poverty that occurs in Indonesia is still high. Therefore, the role of zakat is expected to be a means to alleviate poverty. One way to overcome poverty is to optimize the utilization of zakat, infaq and alms (ZIS) funds. BAZNAS Kotawaringin Regency has several programs, one of which is a program to alleviate poverty and improve community welfare, namely the Kotim Sejahtera program which is engaged in economic empowerment by providing productive assistance to mustahik. This study aims to determine the form of utilization of zakat, infaq and alms funds in the Kotim Sejahtera program at BAZNAS East Kotawaringin Regency and the impact of the Kotim Sejahtera program on the welfare of mustahik. This research is included in the type of empirical legal research, which is a type of legal research that examines the operation of law in society. The approach used in this research is descriptive qualitative. The subjects of this research are Vice Chairman II of Distribution and Empowerment, BAZNAS staff and mustahik recipients of business capital assistance Kotim Sejahtera program. Data collection using interview, observation and documentation methods which were then classified and analyzed by qualitative methods. The results of this study indicate that the utilization of zakat, infaq and alms funds in the Kotim Sejahtera program at BAZNAS East Kotawaringin Regency is a type of economic empowerment program by providing productive business capital assistance in the form of providing business necessities for mustahik. The implementation of this program has been carried out well and is able to achieve the desired goals. The impact of utilization in the program is able to improve the welfare of mustahik as evidenced by the fulfillment of 10 indicators of mustahik welfare. Keyword: Utilization, Zakat, Infaq and Sadaqah Funds, Kotim Sejahtera. Abstrak Penelitian ini dilatarbelakangi oleh permasalahan kemiskinan yang terjadi di Negara Indonesia tercatat masih tinggi. Oleh karena itu, peran zakat diharapkan mampu menjadi sarana untuk mengentaskan kemiskinan. Salah satu cara mengatasi kemiskinan ialah optimalisasi dalam pendayagunaan dana zakat, infak dan sedekah (ZIS). BAZNAS Kabupaten Kotawaringin memiliki beberapa program yang mana salah satunya adalah program untuk mengentaskan kemiskinan dan meningkatkan kesejahteraan masyarakat yaitu program Kotim Sejahtera yang bergerak dibidang pemberdayaan ekonomi dengan cara memberikan bantuan secara produktif kepada mustahik. Penelitian ini bertujuan untuk mengetahui bentuk pendayagunaan dana zakat, infak dan sedekah dalam program Kotim Sejahtera pada BAZNAS Kabupaten Kotawaringin Timur dan dampak program Kotim Sejahtera tersebut terhadap kesejahteraan mustahik. Penelitian ini termasuk ke dalam jenis penelitian hukum empiris, yakni jenis penelitian hukum yang mengkaji bekerjanya hukum di masyarakat. Pendekatan yang digunakan dalam penelitian ini adalah deskriptif kualitatif. Subjek penelitian ini adalah Wakil Ketua II Bidang Pendistribusian dan Pendayagunaan, staf BAZNAS serta para mustahik penerima bantuan modal usaha program Kotim Sejahtera. Pengumpulan data menggunakan metode wawancara, observasi dan dokumentasi yang kemudian diklasifikasi dan dianalisis dengan metode kualitatif. Hasil dari penelitian ini menunjukkan bahwa pendayagunaan dana zakat, infak dan sedekah dalam program Kotim Sejahtera pada BAZNAS Kabupaten Kotawaringin Timur merupakan jenis program pemberdayaan ekonomi dengan cara memberikan bantuan modal usaha produktif yakni dalam bentuk pemberian barang-barang keperluan usaha untuk mustahik. Pelaksanaan program ini telah dilakukan dengan baik dan mampu mencapai tujuan yang diinginkan. Adapun dampak pendayagunaan dalam program tersebut mampu meningkatkan kesejahteraan mustahik yang dibuktikan dengan terpenuhinya 10 indikator kesejahteraan mustahik. Kata Kunci: Pendayagunaan, Dana Zakat, Infak dan Sedekah, Kotim Sejahtera.